Unified system and classification of indicators for integral assessment of the performance and effectiveness of medical care organization at the regional level in the Russian Federation - V. V. Omelyanovskiy; I. А. Mikhailov; D. V. Lukyantseva; Е. S. Samsonova; G. G. Lebedenko (Фармакоэкономика)
Objective: development of a unified system and classification of indicators for an integral assessment of performance and effectiveness of the organization of medical care (MC) at the regional level in the Russian Federation (RF).Material and methods. A systematic search for domestic and foreign scientific publications and a comprehensive analysis of the current regulatory legal acts in the field of health care for the presence of indicators characterizing the effectiveness of MC organization in the RF regions were performed. The search for indicators of effectiveness was carried out in analytical reports based on the results of field events of national medical research centers (NMRC) in the constituent entities of the RF for 2019, 2020 and 2021 in various profiles of MC. In total, 3019 analytical reports on the results of field events and 97 annual public reports on the results of the NMRC activities were analyzed.Results. Three options for classifying indicators were formed: according to the method of obtaining (primary, calculated, secondary qualitative); in relation to the final result (resulting, process (surrogate)); classification of parameters that determine the MC system, including in the context of profiles, forms, types, conditions of MC (18 positions). The proposed unified system and classification of indicators has a number of advantages compared with the Organisation for Economic Cooperation and Development, Centers for Medicare & Medicaid Services and Commonwealth Fund indicators adopted in a number of countries. It was established that international systems use mainly resulting indicators, while the domestic health care system uses exclusively process indicators that are not combined into a single system and are monitored by various departments.Conclusion. The presented approach to a unified system and classification of indicators for an integrated assessment of performance and effectiveness of MC organization allows to determine the priorities for the development of a monitoring system. At the same time, it should be noted that this approach requires further discussion and improvement.